Logical aspects of computational linguistics 6th International Conference, LACL 2011, Montpellier, France, June 29 - July 1, 2011. Proceedings - Pogodalla, Sylvain; Prost, Jean-Philippe.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the 6th International Conference on Logical Aspects of Computational Linguistics, LACL 2011, held in Montpellier, France, in June/July 2011. The 18 revised full papers presented were carefully reviewed and selected from 31 submissions. The papers address a wide range of logical and formal methods in computational linguistics such as type-theoretic grammars, dependency grammars, formal language theory, grammatical inference, minimalism, generation, and lexical and formal semantics.
Electronic reproduction.
Keywords: Computational linguistics -- Congresses; Language and logic -- Congresses; Electronic books